Genetic parameters for egg production in meat quails through partial periods - Ribeiro,Jeferson Corrêa (2017)
ABSTRACT: We estimated genetic and phenotypic parameters for egg production in meat-type quails aiming to propose an optimal age for selection through partial record egg production. Data of 3,503 female quails from two strains (namely, UFV1, with 1,811 and UFV2 with 1,692 females) were used. Egg production was assessed by the number of eggs recorded after 42 days of age and each partial period consisted on 35 days of egg production forward. Covariance components were estimated by using single and bivariate animal model, comprising each partial period of egg production and full egg production period (one year of egg laying). Regarding strain UFV1, heritability estimates ranges from 0.03 to 0.16, and for strain UFV2 0.20 to 0.25. The highest genetic correlation with full egg production was with second period (0.64) for strain UFV1 and with third period (0.47) for UFV2. Therefore, animal selection based on egg production until 112 days for the strain UFV1 and 147 days for the strain UFV2 provided increased genetic gain by reducing generation interval.